An association of neovascular age-related macular degeneration with polymorphisms of CFH, ARMS2, HTRA1 and C3 genes in Czech population - Matušková, Veronika; Zeman, Tomáš; Ewerlingová, Laura; Hlinomazová, Zuzana; Souček, Jan; Vlková, Eva; Goswami, Nandu; Balcar, Vladimir J; Šerý, Omar (Acta ophthalmologica, 2020)
PURPOSE: We investigated associations between neovascular age-related macular degeneration (AMD) and rs10490924 polymorphism of ARMS2 gene (age-related maculopathy susceptibility 2), rs1061170 polymorphism of gene for complement factor H (CFH), rs2230199 polymorphism of gene for complement component C3 and rs11200638 polymorphism of gene for serine protease high-temperature requirement A1 (HTRA1) in the Czech population. METHODS: We analysed samples of DNA from 307 patients diagnosed with neovascular form of late AMD (average age: 73.7 ± 7.7 years) and 191 control subjects, recruited from patients awaiting cataract surgery (average age, 73.6 ± 8.7 years). RESULTS: HTRA1, CFH and ARMS2 genes polymorphisms were found to be related to neovascular AMD in the Czech population. All analysed polymorphisms were statistically significantly associated with neovascular AMD, with stronger associations in females than in males. In whole group, CC genotype of CFH gene polymorphism, TT genotype of ARMS2 gene polymorphism and AA genotype of HTRA1 gene polymorphism showed the greatest risk for neovascular AMD with odds ratios equal to 8.43, 10.07, 9.83, respectively (p < 0.0001). Only CG polymorphism of C3 gene showed statistically significant risk for neovascular AMD. In addition, we observed an association between waist circumference and neovascular AMD in both sexes, which further suggests the significance of excessive abdominal fat as a risk factor of AMD. We found a statistically significant association between polymorphisms in HTRA1, CFH and ARMS2 genes and neovascular AMS in the Czech population. The association was stronger in females than in males. CONCLUSION: We demonstrated a relationship between neovascular AMD and genes for HTRA1, CFH, ARMS2 and C3 in Czech population. To our knowledge, the relationship between these polymorphisms and neovascular AMD in Czech population has never been investigated before.
Keywords: Obesity, Abdominal; Female; gene; Complement C3; komplement C3; ženské pohlaví; jednonukleotidový polymorfismus; lidé; Polymorphism, Single Nucleotide; Macular Degeneration; studie případů a kontrol; Aged, 80 and over; Proteins; High-Temperature Requirement A Serine Peptidase 1; Risk Factors; Sex Factors; proteiny; komplement - faktor H; serinová proteasa HTRA1; Case-Control Studies; Aged; sexuální faktory; Czech Republic; Male; makulární degenerace; rizikové faktory; polymorphism; Česká republika; inflammation; retina; senioři nad 80 let; senioři; mužské pohlaví; abdominální obezita; risk; obesity; Complement Factor H; Humans